Interference of Meloidogyne javanica in the reproduction of Pratylenchus brachyurus in soybean cultivar BRS/MT pintado - Fontana, Lais Fernanda [UNESP]; Arieira, Claudia Regina Dias; Abe, Vinicius Hicaro Frederico; Severino, José Junior; Arieira, Jailson De Oliveira; Monteiro, Raimundo Nonato Farias [UNESP] (Grupo Paulista de Fitopatologia, 2018)
Root-knot nematodes, Meloidogyne spp., and the root-lesion nematode, Pratylenchus brachyurus, are the most common phytoparasites in soybean crop, which usually occur in association in crop areas. However, few studies were conducted on the interaction between these parasites. Therefore, this study aimed to assess the interference of the increase in M. javanica population in the reproduction of P. brachyurus, and the effect of mixed populations on soybean (cultivar BRS/MT Pintado) development. The experiment consisted in inoculating a population of 1000 specimens of P. brachyurus per plant and changing the inoculum level of M. javanica, using zero, 1000, 2000 and 4000 eggs, in two different periods. After 65 days of inoculation, the increase in the initial population of M. javanica reduced by 79 and 73% the final population of P. brachyurus in the different experiments. However, both species significantly increased their populations. When subjected to the same inoculum level, M. javanica was more efficient in reproducing than P. brachyurus. The increase in the number of nematodes reduced the vegetative growth of the plant.

Os nematoides das galhas, Meloidogyne spp., e o nematoide das lesões radiculares, Pratylenchus brachyurus, são os fitoparasitas mais comuns na cultura da soja e comumente ocorrem associados nas áreas de cultivo. Porém, poucos são os estudos da interação existente entre eles. Assim, objetivou-se avaliar a interferência do aumento da população de M. javanica sobre a reprodução de P. brachyurus, e o efeito das populações mistas no desenvolvimento da soja cv. BRS/MT Pintado. O experimento consistiu em inocular uma população de 1000 espécimes de P. brachyurus por planta e variar o nível de inóculo de M. javanica, usando zero, 1000, 2000 e 4000 ovos, e foi conduzido em duas épocas distintas. Após 65 dias da inoculação, observou-se que o aumento na população inicial de M. javanica reduziu em 79 e 73 % a população final de P. brachyurus, nos diferentes experimentos. Porém, ambas as espécies aumentaram significativamente as populações. Quando submetidos ao mesmo nível de inóculo, M. javanica foi mais eficiente em reproduzir-se do que P. brachyurus. O aumento no número de nematoides reduziu o desenvolvimento vegetativo da planta.
Interferência de Meloidogyne javanica na reprodução de Pratylenchus brachyurus em soja cultivar BRS/MT pintado.
Keywords: Glycine max; interactions; root-knot nematodes; root-lesion nematodes; mixed populations; Glycine max; Interações; Nematoides das galhas; Nematoides das lesões radiculares; Populações mistas